Evaluating the psychometric quality of school connectedness measures: A systematic review - Hodges, A.; Cordier, Reinie; Joosten, Annette; Bourke-Taylor, H.; Speyer, R. (Public Library of Science, 2018)
Introduction: There is a need to comprehensively examine and evaluate the quality of the psychometric properties of school connectedness measures to inform school based assessment and intervention planning. Objective: To systematically review the literature on the psychometric properties of self-report measures of school connectedness for students aged six to 14 years. Methods: A systematic search of five electronic databases and gray literature was conducted. The COnsensus-based Standards for the selection of heath Measurement INstruments (COSMIN) taxonomy of measurement properties was used to evaluate the quality of studies and a pre-set psychometric criterion was used to evaluate the overall quality of psychometric properties. Results: The measures with the strongest psychometric properties was the School Climate Measure and the 35-item version Student Engagement Instrument exploring eight and 12 (of 15) school connectedness components respectively. Conclusions: The overall quality of psychometric properties was limited suggesting school connectedness measures available require further development and evaluation.